2015
DOI: 10.1007/s40519-015-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of emotional eating and their weight-loss treatment-induced changes in women with obesity

Abstract: Findings suggest that weight-loss interventions should target specific psychosocial factors to improve emotional eating. The administration of cognitive-behavioral methods through personal contact might be more beneficial for those improvements than self-help formats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
2
10
1
Order By: Relevance
“…These findings contrast with analyses from this same trial including the entire pool of participants (i.e., BMI ≥30kg/m 2 ), which found that poor motivation for physical activity was associated with decreased weight loss [30]. Other studies have found that certain psychosocial characteristics, including higher self-efficacy to initiate exercise [31], emotional eating [32] and lack of autonomous regulation [33], are associated with less weight loss. Our findings suggest that despite having positive intentions and self-belief in their ability to make behavior change, patients with severe obesity may encounter other barriers to weight loss that patients with class I obesity do not experience.…”
Section: Discussioncontrasting
confidence: 66%
“…These findings contrast with analyses from this same trial including the entire pool of participants (i.e., BMI ≥30kg/m 2 ), which found that poor motivation for physical activity was associated with decreased weight loss [30]. Other studies have found that certain psychosocial characteristics, including higher self-efficacy to initiate exercise [31], emotional eating [32] and lack of autonomous regulation [33], are associated with less weight loss. Our findings suggest that despite having positive intentions and self-belief in their ability to make behavior change, patients with severe obesity may encounter other barriers to weight loss that patients with class I obesity do not experience.…”
Section: Discussioncontrasting
confidence: 66%
“…Therefore, according to previous research results obtained by Micanti et al [ 10 ] and Annesi et al [ 66 ], snacking and emotional eating might be crucial for interventions related to changing eating behaviours, but not only for people with excessive weight. By addressing these problematic eating behaviours, future research should include longitudinal research to help recognise better mechanisms to change eating behaviours among individuals with various BMI levels (which may be in different stages of behavior change for weight loss, diet and exercise).…”
Section: Discussionmentioning
confidence: 87%
“…Emotional eating is defined as the tendency to eat more in response to negative emotions [9,10] and it is a risk factor for the development of many eating pathologies, such as binge-eating disorder, bulimia nervosa and food cravings [11,12]. Several studies showed that emotional eating is associated with unhealthy lifestyles, characterized by the consumption of high-calorie and high fat foods, poor weight loss outcomes, weight gain and obesity [13][14][15]. Furthermore, in another study by Wong and Qian (2016), it has also been shown, that shame, as a self-conscious emotion, played an important role in emotional eating.…”
Section: Psychologymentioning
confidence: 99%